AB1089 EVALUATION OF JOINT RHEUMATOLOGY/RADIOLOGY MDT OUTCOMES & THEIR IMPACT ON RHEUMATOLOGY SERVICE. (2nd June 2020) - Ediriweera, A.; Lee, W. P.; Steward, M.; Savanovic-Abel, O.
Abstract : Background: Multidisciplinary team (MDT) discussion between rheumatology and radiology is vital in diagnostic and prognostic management of patients' outcome. Nevertheless, discrepancies of the radiology report and clinical history cause unnecessary confusion and distresses to clinicians and patients. This could potentially affect subsequent clinical management. Objectives: This survey was aimed to evaluate outcomes of rheumatology / radiology MDT discussion and to identify any discrepancies between original reports of the radiology images and amended reports following MDT. We also looked for potential reasons for the discrepancies and their impact on patient and health care resources due to erroneous original reporting. Methods: We looked at all types of images which were discussed in rheumatology/ radiology MDT of University Hospital Plymouth from October 2016 to April 2019. A total of 154 images were randomly selected and their reports were analyzed. The original reports were compared with the addendum made after the MDT and on the rheumatology electronic records. Clinical letters were also looked at to identify changes in follow up and treatment plans after the MDT. Results: The majority of discussed images were X-rays (88). This is followed by 56 MRIs, 8 Ultrasounds and 2 others including CT. After MDT review 38/88 X-rays (43%), 9/56 MRIs (16%) and 1/ 8 USS (13%) reports were amended. 31/38 amended X-ray (82%) and 5/9 amended MRIs (56%) were externally reported originally. In addition, 4 X-rays and 1 MRI reported by Radiology trainees were also amended. Following the MDT outcome, the management plan was changed in 18/38 (47%) amended X-ray reports and 6/ 9 (67%) in amended MRI reports. There were 17 rheumatology referrals by GP that were based on erroneous X-rays reporting and 3 of them were rejected after the MDT. The others were brought to the MDT after the first clinic visit and were discharged subsequently. Conclusion: Joint rheumatology/ radiology MDT discussion makes significant outcome to patient care by minimizing unnecessary investigations and treatment based on erroneous or unclear reporting. Question is raised about efficacy of outsourcing of radiology reporting and need for intensive training for radiology trainees in reporting muscululoskeletal(MSK) images. Since significant numbers of GP referrals were based on erroneous reports, reporting done by MSK radiologists would have reduced unnecessary burden and waste of outpatient rheumatology resources. The images submitted for MDT were selected largely by consultant rheumatologists based on their review of the images and reliance on the original report. Therefore, clinical impact is underestimated in this survey as there were potentially other images not reviewed in MDT that had ended in unnecessary clinical consultation. This survey emphasizes the need and importance of incorporating formal musculoskeletal radiology training into routine rheumatology training program. Disclosure of Interests: None declared